2008
DOI: 10.1177/1524839908323521
|View full text |Cite
|
Sign up to set email alerts
|

A National Patient Navigator Training Program

Abstract: Patient Navigation is an intervention aimed at addressing cancer health disparities by eliminating barriers to diagnosis, treatment, and services. Three major patient navigation (PN) programs (The National Cancer Institute, The American Cancer Society &The Center for Medicare and Medicaid Services) are underway to address the needs of medically underserved cancer patients. There has not been national training with a defined curriculum for patient navigators (PNs). Curriculum for training the PNs was created by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 19 publications
(22 reference statements)
3
108
0
1
Order By: Relevance
“…To ensure uniform navigation practices, navigators participated in annual national training on patient navigation, received bimonthly local training by the research team supplemented by periodic national webinars, and underwent semiannual on-site competency evaluations. 23 After physicians had notified subjects of their abnormal cancer screening test results, navigators contacted subjects and used the care management model to determine what impediments, if any, there were to obtaining the necessary diagnostic follow-up (i.e., any barriers to care). 24 For each subject, navigators (1) …”
Section: The Navigation Interventionmentioning
confidence: 99%
“…To ensure uniform navigation practices, navigators participated in annual national training on patient navigation, received bimonthly local training by the research team supplemented by periodic national webinars, and underwent semiannual on-site competency evaluations. 23 After physicians had notified subjects of their abnormal cancer screening test results, navigators contacted subjects and used the care management model to determine what impediments, if any, there were to obtaining the necessary diagnostic follow-up (i.e., any barriers to care). 24 For each subject, navigators (1) …”
Section: The Navigation Interventionmentioning
confidence: 99%
“…The navigators attended annual and biannual in-person and webinar PNRP training sessions that covered the role of navigators, cancer research, screening, culture and diversity, mapping health system resources, and more. 34 Interactive role play and lecture provided all navigators a common set of tools with which to identify and remove barriers. All navigators received feedback and suggestions based on their role-play exchanges.…”
Section: Patient Navigatorsmentioning
confidence: 99%
“…Evaluation indicated that post-test training scores improved. 34 Locally, Chicago PNRP project leaders observed the navigators' interaction with patients on a weekly basis; project leaders compared their observations on barriers with the navigators' documented barriers. Inconsistencies were discussed and reconciled with the navigator.…”
Section: Patient Navigatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer patient navigators are prevalent, though their roles vary 12,13 . In response to growing demand, The National Cancer Institute conducts a national patient-navigator training program 14 . Peer counseling or navigation refers to support offered to people with cancer by cancer survivors 15,16 .…”
Section: Introductionmentioning
confidence: 99%